p-mTOR, p-4EBP-1 and eIF4E expression in canine prostatic carcinoma - Rivera-Calderón, Luis G. [UNESP]; Fonseca-Alves, Carlos E. [UNESP]; Kobayashi, Priscila E. [UNESP]; Carvalho, Márcio [UNESP]; Vasconcelos, Rosemeri O. [UNESP]; Laufer-Amorim, Renée [UNESP] (Elsevier, 2019)
The mTOR/4E-BP1/eIF4E pathway plays important roles in the neoplastic transformation process and in tumour growth. In men, the mTOR/4E-BP1/eIF4E pathway was described as altered in different tumours, including prostate cancer (PC). Apart from humans, the dog is the only species that develops PC with high frequency and is considered a good model for comparative oncology initiatives. Due to limited information on this pathway in canine tumours, this study aimed to investigate mTOR, 4E-BP1 and eIF4E gene and protein expression in canine PC, as well as in metastatic and normal prostatic tissues, and to evaluate the correlations between gene/protein expression and Gleason score (GS) in PC. A total of 35 formalin-fixed paraffin-embedded (FFPE) samples, including 13 of normal prostatic tissue, 17 PC samples and 5 metastasis samples, were evaluated by immunohistochemistry and qPCR. mTOR gene mutation in the kinase domain was also investigated. We identified higher p-mTOR and eIF4E protein levels in canine PC with higher GS values (≥ 8) and a significant positive correlation in expression between these proteins. eIF4E overexpression was observed in metastasis relative to expression in normal samples. Our data suggest that p-mTOR and eIF4E expression is positively correlated with GS in canine PC, similar to the pattern in humans. More studies of the mTOR/4EBP1/eIF4E pathway should be performed to identify possible correlations of the proteins involved with clinical and pathologic findings in canine PC and the roles of these proteins as therapeutic targets for the treatment of canine PC.
Keywords: Dog; Gleason score; mTOR pathway; Oncology; Prostate cancer